Level of Knowledge of Infectious and Non-Infectious Diseases Material among Darmo Health College Students in Medan - Tri Budiarti, Tri; Daulay, Cahya Aisyah (Jurnal Kesmas Prima Indonesia, 2025)
This study aimed to determine the knowledge level of infectious and non-infectious diseases in students of STIKes Darmo Medan. This study used quantitative descriptive with a survey method. The population of this study was students of STIKes Darmo Medan, totaling students, with proportional random sampling. The sample used was 63 students with a multiple-choice test instrument. The data analysis technique used quantitative description with a percentage to describe the level of student knowledge of infectious and non-infectious diseases. The results of the study obtained results of 16.84% with a total of 11 students in the "very low" category, 42.11% with a total of 20 students in the "low" category, 21.05% with a total of 15 students in the "moderate" category, 12.63% with a total of 10 students in the "high" category, 7.37% with a total of 7 students in the "very high" category. The results showed that the student knowledge of infectious and non-infectious diseases was classified as "Low."